ANALISIS KUALITAS LAYANAN LIVIN’ BY MANDIRI MENGGUNAKAN ELETRONIC SERVICE QUALITY DAN KANO (Studi Kasus : PT Bank Mandiri (Persero) Tbk, KCP Pekanbaru Panam) - Tri Novita Sari; Nofan Hadi Ahmad; Asri Amalia Muti (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2024)
The increasingly rapid competition for digital services in industry 4.0 is no exception in the banking world, encouraging every bank to continue to innovate in its digital services. PT Bank Mandiri as one of the largest banks in Indonesia strives to continue to innovate in its digital services, one of which is Livin' by Mandiri which is useful for making transactions easier for customers anytime and anywhere. However, there are still customer complaints regarding the use of Livin' by Mandiri, including customers at PT Bank Mandiri KCP Pekanbaru Panam demanding quality improvements. Quality analysis of Livin' by Mandiri services using Electronic Service Quality (E-ServQual) and Kano is expected to help in improving the quality of digital services owned by Bank Mandiri. A total of 75 customers as respondents with 28 attributes/questions related to the Livin' by Mandiri, the concluded are "The login feature application with user ID and password before being used by customers for all transactions" is the main service that must be maintained, while the "Cardless Cash Withdrawal Feature Application" is a service that must be prioritized for repairs first.